Structural, ferroelectric and dielectric properties of multiferroic YMnO3 synthesized via microwave assisted radiant hybrid sintering. Issue 5 (May 2019) - Kumar, Manish; Phase, D.M.; Choudhary, R.J.
Abstract: In this work, multiferroic YMnO3 ceramic samples prepared via microwave assisted radiant heating method (at 4 different microwave power percentage: 0, 15, 30 and 50) were studied to investigate their structural, ferroelectric and dielectric properties. In Raman measurement, the A1 Raman scattering line at ∼ 683 cm −1 is much stronger than other Raman modes and dominates the Raman spectra in all samples. The observed Raman modes identify the hexagonal YMnO3 type structure of studied samples. YMnO3 samples prepared at different microwave power displayed variation in ferroelectric polarization. The dielectric constant and dielectric loss tangent variation across different frequencies is also explored for these samples.